2014
DOI: 10.1364/jot.81.000408
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ions of rare-earth metals on the temperature dependence of the luminescence of molecular clusters of silver in oxyfluoride glasses

Abstract: The influence of temperature on the spectral composition and luminescence intensity of oxyfluoride glasses containing molecular clusters of silver and ions of the rare-earth metals samarium and terbium has been investigated. It is shown that introducing these ions into the composition of the glass increases the luminescence intensity of the molecular clusters of silver and the temperature sensitivity of their luminescence intensity. In oxyfluoride glass with molecular clusters of silver and Tb 3 ions, the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(24 reference statements)
0
2
0
1
Order By: Relevance
“…A large variety of glasses have been developed with luminescent centers in the form of molecular clusters (MCs) of silver, [13][14][15][16][17][18][19][20] MCs of copper compounds, [21][22][23][24] and MCs and quantum dots of cadmium and lead chalcogenides. [25][26][27][28] Silicate glasses with neutral silver MCs were chosen from this variety for this paper, since they are optimal in the following parameters: High chemical stability of the glass matrix, high (20-60%) quantum yield 29 of the luminescence of the silver MCs, and spectral coincidence of the luminescence band of the silver MCs with the spectral-sensitivity band of silicon photodiodes.…”
Section: Experimental Techniquementioning
confidence: 99%
“…A large variety of glasses have been developed with luminescent centers in the form of molecular clusters (MCs) of silver, [13][14][15][16][17][18][19][20] MCs of copper compounds, [21][22][23][24] and MCs and quantum dots of cadmium and lead chalcogenides. [25][26][27][28] Silicate glasses with neutral silver MCs were chosen from this variety for this paper, since they are optimal in the following parameters: High chemical stability of the glass matrix, high (20-60%) quantum yield 29 of the luminescence of the silver MCs, and spectral coincidence of the luminescence band of the silver MCs with the spectral-sensitivity band of silicon photodiodes.…”
Section: Experimental Techniquementioning
confidence: 99%
“…Different from the Ag nanoparticles (NPs) that show characteristic surface plasmonic resonance (SPR) absorption, the ML silver clusters consist of only several to hundred silver atoms and only exhibit radiative emission . As an intermediate state lying between single Ag + and Ag NPs, the formation and the size distribution of ML‐Ag cluster is very sensitive to both the glass matrix and the doped RE ions . Recent researches indicated that the ML silver clusters are efficient sensitizer for Eu 3+ and Bi 3+ to enhance their luminescence intensity through direct energy‐transfer (ET) process .…”
Section: Introductionmentioning
confidence: 99%
“…При этом серебро может вводиться в стекло как непосредственно при син-тезе стекла, так и методом ионного обмена (ИО) [6]. В стеклах, содержащих нейтральные МК серебра и ионы редкоземельных металлов, может быть получена высокая температурная чувствительность интенсив-ности люминесценции [7]. В работах [3,8] описаны люминесцентные волокна из стекол с квантовыми точ-ками халькогенидов кадмия, которые могут быть использованы в волоконных датчиках искрения и дози-метрах УФ излучения.…”
Section: Introductionunclassified